Fresnoite oxides : synthesis, crystal chemistry and possible melilite intergrowth - Wong, Chui Ling (2011)
Fresnoites (A2BC2O8) and melilites (A2BC2O7) are layered oxides whose basic structures are modified by crystallographic modulation arising from the need to accommodate pentagonal oxygen rings that cannot fill space without distortion. The modulations are systematized using higher dimensional space groups ( > 3D). Interest in these materials has focused on chemically and/or thermally induced commensurate-incommensurate phase transitions, and provided insights into the nature of interlayer bonding and polyhedral rigidity. Exploitation of this understanding to develop and tune functionality is, as yet, hardly explored. In particular, the application of these oxides as heterogeneous semiconductor photocatalysts has not been considered.